2010
DOI: 10.1375/twin.13.6.567
|View full text |Cite
|
Sign up to set email alerts
|

A Twins Heritability Study on Alpha Hemoglobin Stabilizing Protein (AHSP) Expression Variability

Abstract: Cytotoxic precipitation of free α-globin monomers and its production of reactive oxygen species cause red cell membrane damage that leads to anemia and eventually ineffective erythropoiesis in β-thalassemia. Alpha hemoglobin stabilizing protein (AHSP) was found to bind only to free α-globin monomers creating a stable and inert complex which remains soluble in the cytoplasm thus preventing harmful precipitations. Alpha hemoglobin stabilizing protein was shown to bind nascent α-globin monomers with transient str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This study found that the level of AHSP depended upon the associations of several AHSP haplotypes linking to some clades, possibly associated with sequence variants within the promoter region, including the Oct-1 consensus site [ 63 ]. A classical twin heritability study in unselected twins by the same group found that >45% of AHSP expression was influenced by genetic factors, while almost 30% was influenced by environmental factors [ 64 ].…”
Section: Alpha-hemoglobin-stabilizing Protein (Ahsp): Expression Func...mentioning
confidence: 99%
“…This study found that the level of AHSP depended upon the associations of several AHSP haplotypes linking to some clades, possibly associated with sequence variants within the promoter region, including the Oct-1 consensus site [ 63 ]. A classical twin heritability study in unselected twins by the same group found that >45% of AHSP expression was influenced by genetic factors, while almost 30% was influenced by environmental factors [ 64 ].…”
Section: Alpha-hemoglobin-stabilizing Protein (Ahsp): Expression Func...mentioning
confidence: 99%